ANALISIS RESPON MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS NUSA CENDANA TERHADAP MODEL TUGAS BERBASIS PROYEK - Maria A. Keke; Moses K. Tokan; Andam S. Ardan; Mbing M. Imakulata (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Contemporary learning developments in the 21st century demand adaptations in teaching methods, where project-based assignments foster creativity, collaboration, and real-world problem-solving among prospective biology teachers. Initial observations indicated students lack innovation without lecturer guidance, necessitating response analysis to evaluate effectiveness. This study adopted a descriptive quantitative approach, collecting data through a Likert-scale questionnaire (strongly disagree, disagree, moderately agree, agree, strongly agree) covering 8 aspects: topic understanding, creativity and innovation, collaboration, time management, product quality, project presentation, reflection/process, and benefits. It involved 84 student respondents, with data processed using Microsoft Excel and SPSS version 21.Analysis results showed student responses to the project-based assignment model in contemporary learning lectures fell into the